2008
DOI: 10.1007/s11664-007-0377-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ge22Sb22Te56 and Sb-Excess Ge15Sb47Te38 Chalcogenide Thin Films for Phase-Change Memory Applications

Abstract: A phase-change memory device that utilizes an antimony (Sb)-excess Ge 15 Sb 47 Te 38 chalcogenide thin film was fabricated and its electrical properties were measured and compared with a similar device that uses Ge 22 Sb 22 Te 56 . The resulting electrical characteristics exhibited I reset values of 14 mA for Ge 22 Sb 22 Te 56 and 10.6 mA for Ge 15 Sb 47 Te 38 . Also, the set operation time (t set ) for the device using Ge 15 Sb 47 Te 38 films was 140 ns, which was more than twice as fast as the Ge 22 Sb 22 Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In fact the experimental result of a decreasing R RESET at fixed readout temperature due to increasing Sb concentration, already observed in Refs. [15][16][17] may be directly linked to the modulation of the energy gap as a function of the particular material composition, as already optically measured on thin-film chalcogenide-based alloys [18] as well as electrically measured on amorphous photoconductive materials [19] with the modulation of the Sb concentration and following the same trend. Fig.…”
Section: Program Window Studymentioning
confidence: 56%
“…In fact the experimental result of a decreasing R RESET at fixed readout temperature due to increasing Sb concentration, already observed in Refs. [15][16][17] may be directly linked to the modulation of the energy gap as a function of the particular material composition, as already optically measured on thin-film chalcogenide-based alloys [18] as well as electrically measured on amorphous photoconductive materials [19] with the modulation of the Sb concentration and following the same trend. Fig.…”
Section: Program Window Studymentioning
confidence: 56%
“…To make PCM suitable for applications in automotive technologies the stability of the amorphous phase against recrystallization must indeed be extended above 125 • C, while still preserving a fast phase switching [2]. Changes in the composition of GeSbTe are being investigated, in particular for alloys off the pseudobinary line (GeTe) x (Sb 2 Te 3 ) y [6][7][8][9][10]. For instance, it has been shown that the set and reset currents of PCM devices increase on increasing the Sb content in Ge 2 Sb 2+x Te 5 alloys [6].…”
Section: Introductionmentioning
confidence: 99%